2007
DOI: 10.1002/arch.20164
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two‐step regulation of pheromone biosynthesis by the pheromone biosynthesis‐activating neuropeptide in the moth Heliothis virescens

Abstract: The control of pheromone biosynthesis by the neuropeptide PBAN was investigated in the moth Heliothis virescens. When decapitated females were injected with [2-(14)C] acetate, females co-injected with PBAN produced significantly greater quantities of radiolabeled fatty acids in their pheromone gland than females co-injected with saline. This indicates that PBAN controls an enzyme involved in the synthesis of fatty acids, probably acetyl CoA carboxylase. Decapitated females injected with PBAN showed a rapid inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…These females were left for 6 h [when pheromone titre had declined to a very low level, <0.5 ng (Eltahlawy et al, 2007) ; adjusted to pH=6.8). After 1.5 h, pheromone glands were dissected and analysed for pheromone.…”
Section: Assaysmentioning
confidence: 99%
“…These females were left for 6 h [when pheromone titre had declined to a very low level, <0.5 ng (Eltahlawy et al, 2007) ; adjusted to pH=6.8). After 1.5 h, pheromone glands were dissected and analysed for pheromone.…”
Section: Assaysmentioning
confidence: 99%
“…Recent studies utilizing Heliothis virescens and timecourse experiments (Eltahlawy et al, 2007) demonstrated a rapid decrease ( ¼ ''pull'') in total 16:Acid and stearic acid following treatment with PBAN with a concomitant increase in pheromone from fatty acid stores. If this rapid production of pheromone were caused solely by de novo production of fatty acids, then total saturated fatty acid titers should not decrease initially.…”
Section: Introductionmentioning
confidence: 98%
“…1 Mevastatin was only shown to be active in B. mori(Osawa et al, 1995). 2 ''Push and pull'' theory demonstrated in Heliothis virescens(Eltahlawy et al, 2007).…”
mentioning
confidence: 98%
“…6,12) In heliothine moths, however, PBAN regulates a step (most likely acetyl-CoA carboxylase) in fatty acid biosynthesis. [13][14][15] (iii) In B. mori, the cyclic nucleotide second messenger, cyclic adenosine-3 0 ,5 0 -monophosphate (cAMP), is not involved in the PBAN signal transduction cascade, 16) whereas in heliothine species, the second messenger is a crucial component in PBAN signaling. 4,8) Because numerous biological processes are mediated by fluctuations in the intracellular levels of Ca 2þ , the entry of Ca 2þ into the cell is tightly regulated.…”
mentioning
confidence: 99%